1991
DOI: 10.1002/mrd.1080290309
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis and phosphorylation patterns of bovine oocytes maturing in vivo

Abstract: To investigate protein synthesis and phosphorylation during bovine oocyte maturation in vivo, oocytes were collected at consecutive times after the preovulatory luteinizing hormone (LH) peak. Therefore, heifers treated for superovulation were ovariectomized between 3 and 20 h after the maximum of the LH peak. Subsequently, cumulus-enclosed oocytes, selected from nonatretic follicles greater than 10 mm, were radiolabeled with 35S-methionine or 32P-orthophosphate for 3 h and individually prepared for gel electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The results of the PCA here revealed that oocytes developed in vitro had lower spectral contributions arising from protein vibrations than ovulated oocytes whether obtained from natural ovulations of following a superovulation regimen. These data are consistent with the findings of several authors who have reported lower protein expression in in vitro matured murine [26], bovine [27] and human [28] oocytes, when compared to their in vivo matured counterparts. In certain instances, some proteins were found to be absent in the in vitro developed oocytes, whilst Kim et al [26] specifically identified significantly reduced expression of β-actin and insulin-like growth factor II.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the PCA here revealed that oocytes developed in vitro had lower spectral contributions arising from protein vibrations than ovulated oocytes whether obtained from natural ovulations of following a superovulation regimen. These data are consistent with the findings of several authors who have reported lower protein expression in in vitro matured murine [26], bovine [27] and human [28] oocytes, when compared to their in vivo matured counterparts. In certain instances, some proteins were found to be absent in the in vitro developed oocytes, whilst Kim et al [26] specifically identified significantly reduced expression of β-actin and insulin-like growth factor II.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the fact that nuclear and cytoplasmic maturation of oocytes can proceed independently, both processes need to be coordinated to ensure developmental competence. The path to attain cytoplasmic competence includes buildup and storage of transcripts [1,2], synthesis and accumulation of proteins [3], posttranslational modifications [4], and ultrastructural changes [5]. In primates, cytoplasmic maturation is acquired in fully grown oocytes during the later stages of follicle development [6].…”
Section: Introductionmentioning
confidence: 99%
“…Five levels of oocyte developmental competence were characterized by Sirard et al [3] including the ability to resume meiosis, to cleave upon fertilization, to develop into blastocysts, to induce pregnancy and to generate healthy offspring. Cytoplasmic changes accompanying oocyte growth include mRNA transcription, protein translation and post translational modification [4,5]. Oocytes are complex cells comprising many organelles and molecules, each of which must be in the appropriate state for the egg to be competent to sustain subsequent embryo development [6].…”
Section: Introductionmentioning
confidence: 99%